Telepsychiatry: learning from the pandemic - Greenhalgh, Trisha (Br J Psychiatry, 2022)
This article draws on research and clinical experience to discuss how and when to use video consultations in mental health settings. The appropriateness and impact of virtual consultations are influenced by the patient’s clinical needs and social context as well as by service-level socio-technical and logistical factors.